2014
DOI: 10.3748/wjg.v20.i20.6024
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome: Relations with functional, mental, and somatoform disorders

Abstract: This review describes the conceptual and clinical relations between irritable bowel syndrome (IBS), other functional, somatoform, and mental disorders, and points to appropriate future conceptualizations. IBS is considered to be a functional somatic syndrome (FSS) with a considerable symptom overlap with other FSSs like chronic fatigue syndrome or fibromyalgia syndrome. IBS patients show an increased prevalence of psychiatric symptoms and disorders, especially depression and anxiety. IBS is largely congruent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
22

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 72 publications
8
70
0
22
Order By: Relevance
“…The excessive comorbidity found in our IBS patients is consistent with the results of previous studies (4)(5)(6). The high prevalence of anxiety and depression confirms other reports (5,8,30) and emphasizes the importance of psychological assessment and treatment as part of clinical management of IBS patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The excessive comorbidity found in our IBS patients is consistent with the results of previous studies (4)(5)(6). The high prevalence of anxiety and depression confirms other reports (5,8,30) and emphasizes the importance of psychological assessment and treatment as part of clinical management of IBS patients.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have shown a considerable overlap of IBS with gastroesophageal reflux disease (GERD) and functional dyspepsia (FD) (2,3). In addition, nongastrointestinal somatic disorders and psychiatric disorders occur frequently in IBS (4,5). Comorbidity of IBS has been associated with increased use of health resources, impaired quality of life and poor outcome (6).…”
Section: Introductionmentioning
confidence: 99%
“…33 In our study, psychiatric disorders were seen in about 84.4% of IBS patients. This is quite high compared to the prevalence seen in western studies where the percentage of psychiatric disorders ranges from 40.0-60.0%, 34,35 but is comparable to the rates seen in Indian studies. 36 In the study done by Prashant Singh et al 36 in 2012, comorbid psychiatric disorders were found in 79.9% cases of IBS, which was considerably higher compared to 34.3% seen in controls.…”
Section: Discussionmentioning
confidence: 77%
“…In fact, patients fulfilling criteria for one syndrome often do it for others. At present, diagnostic criteria of FSS require a history of unexplained physical complaints, including several pain or pain-related symptoms (at least four), usually beginning before 30 years of age, persisting years (but, at least 6 months) and leading to significant impairment of individual global functioning, which usually carries to treatment seeking [33][34][35]. Therefore, the phenomenological denominations are being overcome, and it is supposed that all FSS might recognize similar pathological mechanisms.…”
Section: …On Vaccines and Functional Somatic Syndromes (Fss)mentioning
confidence: 96%